ANALISIS KEAMANAN WEBSITE SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN MENGGUNAKAN METODE VULNERABILITY ASSESMENT - Tara Rizkayanti Tara; Yunanri W (Universitas Teknologi Sumbawa, 2023)
Website is an information page that is provided via the internet so that it can be accessed throughout the world as long as internet activity on a device is connected. Information security on a website is the most important at this time, including the website of the Ministry of Home Affairs in the field of population and civil registration which provides information about community personal data. This problem is very important if it is accessed by irresponsible people. The method used in this study is the Vulnerability Assessment method. This research has found information related to the target website and several vulnerability warnings after testing a vulnerability scanner with a high level of risk so that the research recommends fixing the vulnerability to minimize security holes exploited by hackers. Testing was carried out using Kali Linux and OWASP ZAP. Keywords: Security, Website, Dukcapil, Kali Linux, OWAPS ZAP